Goethe abwärts : Deutsche Jungs etc. : Sammlung Falckenberg = Goethe on decline. German boys etc. : the Falckenberg collection - Zybok, Oliver; Helsinki City Art Museum, Helsinki; Mönchehaus Museum für moderne Kunst, Goslar (Goslar Helsinki : Helsinki City Art Museum Helsinki Mönchehaus Museum für moderne Kunst Goslar, 2005)
Acconci, Vito ; Ackermann, Franz ; Baruchello, Gianfranco ; Blume, Bernhard Johannes ; Bock, John ; Bonin, Cosima von ; Brus, Günter ; Büttner, Werner ; Dion, Mark ; Dzama, Marcel ; Eisenman, Nicole ; Feldmann, Hans-Peter ; Fischer, Urs ; Förg, Gunther ; Grommek, Joachim ; Grünfeld, Thomas ; Hartmann, Klaus ; Herold, Georg ; Hirschhorn, Thomas ; Jankowski, Christian ; Kelley, Mike ; Kippenberger, Martin ; Kolk, Douglas ; Krawen, Hendrik ; Land, Peter ; van Lieshout, Erik ; Lucander, Robert ; McCarthy, Paul ; Meese, Jonathan ; Melgaard, Bjarne ; Niehus, Hans ; Oehlen, Albert ; Paeffgen, C.O. ; Parker, Erik ; Pettibon, Raymond ; Pflumm, Daniel ; Polke, Sigmar ; Prince, Richard ; Reski, Gunter ; Richter, Daniel ; Richter, Gerhard ; Roth, Dieter ; Rühm, Gerhard ; Schmit, Tomas ; Schwarzkogler, Rudolf ; Schwontkowski, Norbert ; Skreber, Dirk ; Slominski, Andreas ; Streyl, Annette ; Strode, Thaddeus ; Swansea, Ena ; Tillmans, Wolfgang ; Vater, Markus ; Volkmann, Herbert ; West, Franz
Publikation anlässlig Aussettungen 'Goethe abwärts : Deutsche Jungs etc. : Sammlung Falckenberg' im Helsinki City Art Museum in Helsinki, 15.10.2005 - 15.01.2006 und im Mönchehaus Museum für moderne Kunst in Goslar,14.05.2006 - 06.07.2006
boek